The Function of b+yh in Jonah 4 and Its Translation - Kim, Yoo-Ki (2009)
Most modern translations render b+yh in Jonah 4,4 as a predicate. However, traditional grammars take its function as an adverb that modifies the meaning of the verb, suggesting its translation as a degree adverb. Linguistic considerations support the latter option. This line of understanding opens up a possibility to interpret Yahweh’s question in Jonah 4,4 not as a confrontation but as an expression of consolation and compassion toward his prophet.
Keywords: Jonah 4,4; confrontation; Compassion; Consolation